PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 2 LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Ismawati Ismawati; lazim.N lazim.N; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low mathematics learning outcomes of students, with an average grade 56.75. Among students of 20 people only 7 students who completed reached KKM with classical completeness 35%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes Mathematics Elementary School fourth grade students 2 Muda District of Siak Kecil Lubuk Bengkalis by applying the model of Problem Based Learning. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the increase in the number of students who reach the KKM of 7 people on the base score to 13 people in the first cycle and increased to 18 people in the second cycle. This means that the sample classes have been completed in the classical. An increase in the average learning outcomes of basic score is 56.75 into 63.25 and 76.75 in the first cycle in the second cycle. An increase in the activity of the teacher. At the first meeting of the first cycle of activity percentages of teachers is 65,00%, 75,00% second meeting. While the second cycle the first meeting with the percentage of 85,00%, and the second meeting increased 90,00%. While the student activity also increased that the first meeting of the first cycle of the percentage of student activity is 60,00%, 70,00% second meeting, the first meeting of the second cycle of 75,00% and a second meeting fixed with an average 85,00%. Results of the study in class IV SDN 2 Muda District of Siak Kecil Lubuk Bengkalis prove that the application of the model Application of Problem Based Learning Model to improve learning outcomes Maths grade IV SDN 2 Lubuk Young Bengkalis District of Siak Kecil.Keywords: Problem Based Learning Application, Mathematics and PTK Learning Outcomes.